PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIBEL PEMODERASI (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016) - Julia Ballo, Femmy (MONETER, 2020)
This research made to understand and to analyis if profitability have a relevant effect on firm value and the impact of managerial ownership on firm value with profitability. This research  performed on mining companies that recorded in Indonesia Stock Exchanged in the year 2012-2016. Technique sampling using purposive sampling. Data analysis technique using multiple linier regression. And for the hyphotesis using t test with help from software SPSS statistics 23.0. The result of this research explains that profitability have a significant impact on firm value. It means if profitability increasing then the value firm will increase too and the otherwise if firm value is decreasing then profitability will decrease too. While managerial ownership have a significant and negatif effect to relationship on profitability with firm value. It means that if managerial ownership is increasing then it will decrease the firm value. This result support theory Demsetz (1983), Fama dan Jensen (1983) which shows that in some stages the firm value not always have positive linier related on managerial ownership level.